Konsep Pendidikan Karakter Berbasis Ilmu Hikmah Pada Institut Parahikma Indonesia (IPI) Gowa - Abd. Syukur Abu Bakar (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2017)
This article elaborates on the implementation of character-based science education at the Institute of Parahikma Indonesia (IPI) Gowa. The results of this qualitative research indicate that the implementation of character education based on the science of wisdom at the Institute of Parahikma Indonesia (IPI) Gowa is always associated with the five pillars of development, which initially has been preceded by the strengthening of students' understanding of the nature of creation itself on earth. Problems encounter includes three aspects, in this case, the science of wisdom that has not been socialised widely, the understanding of lecturers who have not maximized, and the limitations of students in understanding the effects of several factors. The solution then is to intensify the integration of the science of wisdom on the five pillars of development in a civilized, intelligent, and thriving shrine.